Belajar Nilai-Nilai Kearifan Lokal dalam Penataan Ruang Kampung Adat Bena - Grace Megumi Maran, Mary; Theresia Geme, Maria; Peter Lay, Benediktus (Perspektif Hukum, 2024)
Spatial planning is one of the elements to realize a harmonious life. Spatial planning can be guided by national law and local wisdom. The purpose of this study is to determine and analyze the implementation of spatial planning in Kampung Adat Bena based on local wisdom. In addition, this study aims to determine and analyze the correlation between the implementation of spatial planning in Kampung Adat Bena based on local wisdom with regulations governing spatial planning. This research is an empirical legal research with the approach of legal sociology, legal history, and legislation. The results show that the implementation of spatial planning in Kampung Adat Bena based on local wisdom consists of a planning process, implementation of plans that produce components or areas, as well as prohibitions and sanctions based on local wisdom values adopted by the community. The value of local wisdom such as mutual cooperation, togetherness, justice, benefits, environmental balance, and harmony between Ga'e Dewa and indigenous peoples through the intermediary Ine Ebu. In addition, there are several components in the implementation of spatial planning in Kampung Adat Bena based on local wisdom that have a correlation with laws and regulations on spatial planning. However, the implementation of spatial planning in Kampung Adat Bena based on local wisdom also has several characteristics that are different from those regulated in the laws and regulations on spatial planning.